PENGARUH STRES KERJA DAN KOMPENSASI KARYAWAN TERHADAP TURNOVER INTENTION DENGAN LINGKUNGAN KERJA FISIK SEBAGAI MODERASI - Worang, Bertha Aprillyanti Jesiecca; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 9 No 5 (2020)DO - 10.24843/EJMUNUD.2020.v09.i05.p06, 2020)
This study aims to determine the effect of work stress and employee compensation on turnover intention with the physical work environment as a moderating variable. The research sample was determined as many as 147 respondents using a sampling technique that is saturated sample. The analysis technique used is moderated regression analysis. This research The management of the Mercure Legian-Bali Hotel must continue to reduce work stress and compensation of employees within the company so that employees feel safe and comfortable and can be committed to the company, so that it will reduce turnover intention at the Mercure Legian-Bali Hotel. The results showed that work stress had a positive and significant effect on turnover intention at the Mercure Legian-Bali Hotel. Employee compensation has a positive and significant effect on turnover intention at the Mercure Legian-Bali Hotel. The physical work environment moderates the effect of work stress on turnover intention at Mercure Legian-Bali Hotel and the physical work environment moderates the effect of employee compensation on turnover intention at the Mercure Legian-Bali Hotel. Keywords: turnover intention, work stress, employee compensation, physical work environment